2021
DOI: 10.1097/tp.0000000000003501
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Propionic Acidemia: Evidence From a Systematic Review and Meta-analysis

Abstract: Background. The worldwide experience of liver transplantation (LT) in the treatment of propionic acidemia (PA) remains limited and fragmented. This review aims to provide a comprehensive and quantitative understanding of posttransplant clinical outcomes in PA patients. Methods. MEDLINE, Embase, and the Cochrane Library databases were searched for studies focusing on PA patients who underwent LT. The pooled estimate rates and 95% confidence intervals (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Despite following a strict protein restriction and pharmacological intervention, PA patients still suffer frequent metabolic decompensations and subsequent devastating long-term complications [ 6 , 7 , 18 ]. As a kind of enzyme replacement therapy, LT has been performed in 67 PA patients with 75 liver grafts to date [ 10 , 11 , 13 15 , 19 34 ]. The overall patient and graft survivals were 80.6% and 72.0%, respectively (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite following a strict protein restriction and pharmacological intervention, PA patients still suffer frequent metabolic decompensations and subsequent devastating long-term complications [ 6 , 7 , 18 ]. As a kind of enzyme replacement therapy, LT has been performed in 67 PA patients with 75 liver grafts to date [ 10 , 11 , 13 15 , 19 34 ]. The overall patient and graft survivals were 80.6% and 72.0%, respectively (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic artery thrombosis (HAT), one of the most life-threatening LT-related complications, is more frequent in pediatric LT, with an estimated rate of 4–8% [ 35 ]. However, the overall rate of HAT in historical PA cases was significantly high at 17.5% [ 11 ]. Therefore, it was once believed that patients with PA are more prone to develop HAT after LT [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of patients with monogenic metabolic liver diseases (such as urea cycle disorders, maple syrup urine disease, MMA, and PA) undergo LT worldwide [17][18][19][20][21]. The explanted livers from those liver transplant recipients with noncirrhotic liver-based metabolic disorders are morphologically, structurally, and functionally normal except for definite metabolic deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation has been used for patient with frequent metabolic decompensations and was shown to be beneficial in propionic acidemiarelated dilated cardiomyopathy. 2 However, progression of cardiomyopathy, or, in rare cases, new-onset dilated cardiomyopathy in the immediate post liver transplant period are now considered well-known complications. Interestingly, Berry et al reported the first case of recurrent dilated cardiomyopathy 3 years after liver transplant.…”
mentioning
confidence: 99%